The book, the tourist and the corpse in the garden: object lessons from Julian Barnes' Flaubert's Parrot and Michel Houellebecq's La Carte et le Territoire. Issue 6 (2nd June 2020) - Evans, Nicola
ABSTRACT: At first sight, Julian Barnes and Michel Houellebecq are two authors with little in common, but this article uncovers a shared interest in the life of objects and their capacity to shape and sometimes eclipse the subject. Both Flaubert's Parrot and La Carte et le Territoire raise compelling questions about subject object relations and their special relevance for the institution of authorship. In a reading that tracks the novels' common concerns with tourists, copies and dead authors, I trace the lineage of these concerns back to eighteenth century debates over the relationship between authors and the material book and forward to new anxieties surfacing as the anticipated death of the material book reanimates questions of what makes an author. By foregrounding the role of tourists in literary culture, both novels challenge the conventions of anti-tourist discourse, inviting us to consider whether tourists played a part in bringing authors to life, and whether they may perform a similar service for the book.